The Picture Storybook of Pancasila Values as the Formation of National Character in Pancasila and Civics Education Learning Class Five of Elementary School in Indonesia - Zakiah, Linda; Komarudin; Herawati, Eti (JTP - Jurnal Teknologi Pendidikan, 2024)
The Pancasila is five life principals of Indonesian and it has been crafted from the ancestor. The Indonesian independence fighters had been trying to create the Pancasila and now it is officially the Indonesian life principals. As the teachers, the Pancasila are compulsory to be taught and delivered to the schools in all levels including elementary schools. One of the main issues among teachers across Indonesia is that it is difficult to transfer Pancasila values to the students because it is considered to be character and it needs a habit to measure how student understand about the values. The aim of this study is to provide a teaching method for elementary school students when learning Pancasila values through the storybook. The values of Pancasila is closely related to the moral of Indonesian. The method used in this research is mix method with Research and Development (R&D) approach and also using ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. This model is designed to create a new learning model for delivering Pancasila values to the students. The data has been collected from 30 students, and one elementary school teachers. The techniques used is questionnaires, interview, and classroom observation. The finding shows that the storybook is effectively used to transform the knowledge of Pancasila values to the students and one of the book called “sahabat toleransi” or a tolerance friends shows that having a friends can be part of Pancasila values. Therefore, it can be concluded that Pancasila values can be taught through some other ways and the picture storybook can be an option for the teachers to teach about it.